PENINGKATAN KEMAMPUAN MEMBACA Al-QUR’AN SISWA MELALUI METODE TALAQQI PADA MATA PELAJARAN AL-QUR’AN HADIS KELAS VIII DI MTS PELAWAN KABUPATEN SAROLANGUN - Azmi, Ulil; Juliana, Rina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This thesis is motivated by the concern of Quran and Hadith teachers regarding the low Quran reading ability of eighth-grade students at Madrasah Tsanawiyah Sa'adah Pelawan, Sarolangun Regency. This condition is a serious problem for teachers because the ability to read the Quran is a basic competency that every student must possess. The research method used in this study is Classroom Action Research (CAR), which refers to the Kemmis and Mc Tangar model, namely with the stages of planning, action, observation, and reflection. This research was conducted collaboratively, where the researcher acted within the classroom and was assisted by the Al-Qur'an Hadith subject teacher and colleagues in observation and documentation activities. The results of this study indicate an increase in each cycle. In Cycle I, the observation results of teacher activity in the first meeting were 45% and increased to 59% in the second meeting. Furthermore, in Cycle II, there was another increase, namely 70% in the first meeting and reaching 80% in the second meeting. This increase is in line with the results of student activity observations, where in Cycle I the value obtained was 54% and increased to 81% in Cycle II. In addition, an increase was also seen in students' ability to read the Qur'an. In Cycle I, there were 8 students or (53.33%) who achieved the minimum mastery criteria (KKM). In Cycle II, the increase obtained was very significant, with the number of students who achieved mastery increasing to 13 students or (86.66%). Based on these results, it can be concluded that the application of the talaqqi method has proven capable of improving students' ability to read the Quran in Quran Hadith lessons for class VIII at Madrasah Tsanawiyah Sa'adah Pelawan, Sarolangun Regency, Jambi Province.